A Structural Equation Model of Factors Influencing Students’ Decisions in Choosing Souphanouvong University - PHAIGNAVONG , Somechay; VANG, Khammee; LAMPHAIPHANH, Ketsalinh; PHETSOMBATH, Sengdao; ONSENGTAVANH, Fongmany (Souphanouvong University Journal Multidisciplinary Research and Development, 2020)
The purpose of this research was to develop and test the Structural Equation Model of factor influencing students’ decisions in choosing Souphanouvong University. The key participants were students who passed or completed year7 in high schools in 8 northern provinces of Lao PDR and were selected as the sample, academic year 2019-2020. There were 160 students including 52 females and quota method was used in order to obtain equal proportions in each province. The tool applied in this study was the questionnaire as it was a quantitative research using Second order confirmatory Factor Analysis plus program Amos version 21 with Parameter estimation and the estimation of Maximum Likelihood Value. The result of Second order confirmatory Factor Analysis could be concluded the developed structure equation model was well consistent with the empirical data by the goodness of fit indices of Degree of freedom (DF) = 43, =1.891, GFI = 0.921, CFI = 0.912, RMR = 0.035, RMSEA= 0.075.